Use of EZProxy to access international journals among students of Library and Information Science, University of Indonesia - Dwi Kusuma, Rusdiyah Ciptaning (Record and Library Journal, 2016)
Studentâs magister is one of user library university of Indonesia those who need information regarding duty as carried out college. With different backgrounds students as, made they need facilities sources of information easy and efficient. The library University of Indonesia the provision of information service, including service online reference to access the international journal address URL through: http: // remote-lib.ui.ac.id (EZProxy to access international journals). This service is facilities remote access, connected with resource at a network central from one location. Students can access journal electronic wherever and anytime simply by making log-in through single sign on. Synthesis a problem in this research is to find how the facility of an EZProxy ui by student magister library and science university of Indonesia? For the purpose to get the facility of a remote lib ui to access the international journal of student magister library science. The result of this research can be a useful tool as input to studentâs library science to develop study would check in the field of library services. Research locations in university Indonesia, election student magister library science, because have a background various activity. With a population of consists of 25 students. And techniques the sample collection by using non probability of sampling with the methods purposive sampling. The sample in this research were informants ever use the service of EZProxy (http: // remote-lib.ui.ac.id) at least once. The majority of informants interviewed 4 people with distribution 2 men and women 2. Technique the data collection was done in two ways that is observation and interview. The next step is to analyzed data. Analysis of data done by means of transcrip the results of interviews, then the data reduced, presentation of data and the withdrawal of conclusion. This research result indicates that the utilization of EZProxy to access international journals by student magister library of science university of Indonesia based on (1) ease in search of articles the international journal, (2) are provided free of charge by a library university of Indonesia so it is more efficient. (3) Can be accessed wherever and anytime, (4) the utilization is very easy, not convoluted (5) Simple, summarized in one online database. So users not get confused. Key words: library, service, information, journal, userÂ